Characteristics of transcriptome and chromatin accessibility in the peripheral blood after acute hypoxia exposure - Kuo Zeng; Pei-ru Yuan; Jin-feng Xuan; Lai-xi Zhao; Xiao-na Li; Jun Yao; Dong Zhao (BMC Biology)
Abstract Background Human responses and acclimation to the environmental stresses of high altitude and low oxygen are multifaceted and regulated by multiple genes. However, the mechanism of how the body adjusts in a low-oxygen environment is not yet clear. Results Hence, we performed RNA sequencing (RNA-seq) and ATAC sequencing (ATAC-seq) to observe the changes of transcriptome and chromatin accessibility in the peripheral blood of eight individuals at 1 h post adaptation in a simulated plateau environment with 3500 m and 4500 m altitude, respectively. Differential expression analysis and the Boruta algorithm identified differentially expressed genes (DEGs) and differentially accessible regions (DARs) associated with hypoxia adaptation. Specifically, RNA-seq identified 93 and 7 DEGs after 1 h post adaptation with 3500 m altitude and 45 and 8 DEGs after 1 h adaptation with 4500 m. Additionally, ATAC-seq screened 12 and 4 DARs in 3500 m altitude adaption and 15 and 5 DARs in 4500 m altitude adaption. Moreover, the combined analysis of RNA-seq and ATAC-seq revealed that 10 hub genes were independently identified from the protein–protein interaction (PPI) network for each altitude. Gene enrichment analysis displayed that most hub genes were related with hypoxia pathways. Conclusions Our results can provide the reference for the early response of the organism to hypoxic adaptation.